PRODUCTION AND EVALUATION OF POLYCLONAL ANTIBODIES AGAINST HOMOLOGOUS CITRUS TRISTEZA VIRUS (CTV) ISOLATES FROM PAKISTAN - Z. Abbas; S. Hameed; B. Lockhart; S. Bratsch; N. Olszewski; Dur-e-shahwar; M. A. Rehman; S. M. Saqlan Naqvi (Journal of Animal and Plant Sciences, 2020)
Citrus tristeza virus (CTV) is a plant pathogenic virus first reported infecting citrus plants in the 1930’s in Brazil and Argentina and is now widely spread through all citrus growing areas. A CTV isolate from an infected Pakistani sweet orange tree was selected for sequencing to subsequently produce recombinant CTV coat protein. The purified recombinant CTV coat protein was used as an antigen for the production of polyclonal antisera in rabbits. The antisera were tested in direct antigen coating enzyme linked immunosorbent assay (DAC-ELISA) against various CTV isolates from Pakistan and T-30 from the USA. The antisera reacted strongly in DAC-ELISA with both homologous and heterologous isolates of CTV from infected citrus leaf and bark tissue. These antisera were compared with a commercially available ELISA kit and were more sensitive to Pakistani isolates of CTV than the commercial ELISA kit. An inexpensive virus-free testing and certification program using the antisera produced here would provide farmers with the knowledge to eliminate CTV infected and unproductive trees, which could then be replaced with healthy young trees. The implementation of such a scheme would reduce the incidence of CTV in citrus orchards, reduce yield losses caused by CTV, and could lead to the elimination of CTV from Pakistan
Keywords: CTV; DAC-ELISA; Antibodies; Polyclonal antisera; Coat protein